A study of grammatical awareness of the first year students majoring in English, Special Program, Faculty of Liberal Arts and Science, Kasestsart University, Kamphaeng Saen Campus - Srinon, Udomkrit (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 2 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2018)
This classroom study aimed to focus on the basic grammatical awareness of the first year students majoring in English in the special program. The research methodology was concerned with the structured survey which involved the grammatical awareness of the students concerned throughout the first semester, 2013 It also aimed to develop and adjust the teaching material set to be more effective and up to dated. The study was based on the survey on the grammatical topics which were outlined in the course which consisted of 5 chapters; Chapter 1 Principle elements of the sentences; Chapter 2 Noun and articles; Chapter 3 Verbs and verbals; Chapter 4 Pronouns, substitution and ellipsis and Chapter 5 Adjectives and adverbs. Findings of the study indicated that the students in all groups rated the grammatical units and sub-topics in different degrees. The mean score of the rating in overall picture is 2.28 which is at the moderate level (SD = 0.61). The students rated Chapter 1, 2 and 3 with toe moderate mean of 2.37, 2.34 and 2.33 (SD = 0.60 in three chapters). However, for the mean scores in Chapter 4 and 5, they are 2.17 and 2.17 (SD = 0.66 and 0.61) respectively. It is recommended that there should be the order of grammatical topics from the most easiest to the most difficult. There might be new topics at the end of the order in order to make students learn the structures systematically and lead them to the preparation for next courses related.